Strategi Pemberdayaan Generasi Muda dalam Gerakan Zero-waste Berbasis Bank Sampah - Suci Nurpratiwi; Faza Sabila Firdaus; Al Bani Ridho Pratama; Muchammad Faqih; Nur Faizah (Penerbit Goodwood, 2026)
Purpose: This study aims to explore youth empowerment strategies through a zero-waste movement based on waste bank management, highlighting the role of young people as agents of change in building sustainable urban environment. Methodology: This activity employed the Participatory Action Research method through dialogue, discussion, and hands-on practice in waste management. Fifteen participants, members of the youth organization in Bukit Duri, Jakarta Selatan, actively participated in this activity. Data were collected through observations, interviews, and documentation. The data were then analyzed through data collection, categorization, display, and conclusions. Findings: This community service activity was implemented through the socialization of environmental issues, involving Karang Taruna (youth organization) in the zero-waste movement, and creative practices in waste recycling. The activity also demonstrated that key empowerment strategies contributed to positive behavioral changes regarding sustainable waste management practices. Conclusions: The findings indicate that empowering youth through continuous training, collaboration with waste banks, and participatory practices can strengthen their role as agents of change in promoting zero-waste lifestyles. This approach fosters long-term sustainability and supports the creation of environmentally conscious community. Limitations: This study was limited to a specific urban area and youth group, which may affect the generalizability of the findings to broader populations or rural contexts. Contributions: This study provides insights into effective community-based youth empowerment models in the environmental sector. This study offers practical strategies to enhance youth participation in waste management.